2012
DOI: 10.1159/000337660
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Better Classify NSAID Hypersensitivity Reactions? – Validation from a Large Database

Abstract: Background: Hypersensitivity to nonsteroidal anti-inflammatory drugs (NSAIDs) is one of the most common drug hypersensitivities. Several clinical subtypes have been distinguished depending on symptomatology (respiratory, cutaneous, anaphylaxis), timing (immediate, delayed), underlying chronic disease (asthma, chronic urticaria) or putative mechanism of the reaction (allergic, nonallergic mediated). The aim of the present study was to better classify the many hypersensitivity reactions to NSAIDs. Methods: In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 37 publications
(24 reference statements)
4
66
0
1
Order By: Relevance
“…Research has shown that up to 40% of NSAID HS reactions are selective [12,13,20,34,35,41], and our results are in line with this findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Research has shown that up to 40% of NSAID HS reactions are selective [12,13,20,34,35,41], and our results are in line with this findings.…”
Section: Discussionsupporting
confidence: 93%
“…Sánchez-Borges et al [13 ](40%), Caimmi et al [20 ](39%), and Nissen et al [30 ](40%)[.] However, some studies indicate that, nowadays, acetylsalicylic acid is not the most common drug involved in HS, and they refer to propionic acid derivatives, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown a possible specific genetic profile in patients with both chronic urticaria and NSAID hypersensitivity [25,26,27]; it would be interesting to establish whether otherwise normal multiple NSAID reactors also show the same profile. Recently, a new classification of NSAID hypersensitivity reactions has been suggested [1], and subsequent amendments have been proposed [28]. It is possible that in the light of the finding of this study, some further changes are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients single NSAID induced reactions usually do not have an underlying chronic cutaneous or respiratory disease, but may have a history of hypersensitivity to food or other drugs. 7 In contrast to single NSAID induced reactions, a chronic respiratory disease (asthma/rhinosinusitis/nasal polip) or cutaneous disease (chronic spontaneous urticaria) exists in patients with NSAID-exacerbated respiratory disease or NSAIDsexacerbated cutaneous disease which are both cross-reactive type of NSAID hypersensitivities. Case 2 and Case 3 are noteworthy for their underlying chronic diseases but single NSAID induced reactions.…”
Section: Discussionmentioning
confidence: 99%